2013
DOI: 10.1039/c3cs60180c
|View full text |Cite
|
Sign up to set email alerts
|

Control of chemical reactions and synthesis by low-energy electrons

Abstract: Controlling the outcome of reactions is a central issue of chemical research. Physical tools can achieve this if they are able to precisely dissociate specific bonds of a molecule. However, to control synthesis, such tools must induce the formation of new bonds between two reactants to yield a more complex product. In the ideal case of an atom efficient synthesis, this product would contain all or at least most of the initial material. An electron beam is a physical tool that is capable of preparing molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
154
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 47 publications
3
154
0
3
Order By: Relevance
“…[3,4] However,i nc ondensed phase where polarization forces stabilize the charge,the radical anion may also survive. [3,4] As neutral excitation processes are absent below roughly 4eVinboth C 2 H 4 and H 2 O, [11] such anionic processes must be responsible for the ethanol yield at low E 0 values. DEA processes for H 2 Oi nt he gas phase occur around 7eV, 9eV, and 11 eV [12] and thus above the range of E 0 values concerned here.Noproduction of OHC radicals occurs below 5eV.…”
mentioning
confidence: 97%
“…[3,4] However,i nc ondensed phase where polarization forces stabilize the charge,the radical anion may also survive. [3,4] As neutral excitation processes are absent below roughly 4eVinboth C 2 H 4 and H 2 O, [11] such anionic processes must be responsible for the ethanol yield at low E 0 values. DEA processes for H 2 Oi nt he gas phase occur around 7eV, 9eV, and 11 eV [12] and thus above the range of E 0 values concerned here.Noproduction of OHC radicals occurs below 5eV.…”
mentioning
confidence: 97%
“…It has been shown that these electron beam induced processes can be performed on almost any kind of substrate [28]. Recently, Bohler et al [29] reviewed low-energy, electron-initiated molecular syntheses and their applications in the modification of surfaces. In summary, irradiation of materials with an electron beam in a TEM can be used to fabricate nanomaterials and to investigate their morphology, structure, and chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In the condensed phase experiments, a multilayer film of TFAA is deposited on a cryogenic metal substrate and then irradiated by an electron beam at a particular energy. Reactions in the condensed material are then probed by thermal desorption spectrometry (TDS) [2][3][4]. The gas phase experiments are carried out under single collision conditions, i.e., the recorded fragment ion is the result of a single collision between an electron and the molecule resulting in resonant electron attachment and the subsequent unimolecular decomposition of the transient negative ion.…”
Section: Introductionmentioning
confidence: 99%
“…a e-mail: kopyra@uph.edu.pl electrons [4][5][6], the condensed environment may also retain immediate products of the dissociative electronmolecule encounter. DEA reactions have so far been studied on many compounds and, in particular, on halogenated molecules because of their well-documented electron scavenging properties [1,7].…”
Section: Introductionmentioning
confidence: 99%